Agency Manifestations in Schoolchildren and Their Involvement in Participatory Budgeting - Mikhail E. Goshin; Pavel S. Sorokin; Boris V. Kupriyanov (Интеграция образования)
Introduction. Education plays a key role in shaping the younger generation’s agency, i.e. their proactive attitude and ability to constructively transform social reality. In this context, it is important to understand how involving schoolchildren in decision-making processes, such as school participatory budgeting, can contribute to the development of their personal responsibility and initiative. However, these practices have not been practically investigated in the context of students’ agency, and there is a lack of empirical evidence on how these initiatives can solve real problems and improve the school community. The aim of the study is to investigate the agency of schoolchildren involved in school participatory budgeting, with an emphasis on identifying the motives and effects of this activity.